A Patient With Pyruvate Carboxylase Deficiency and Nemaline Rods on Muscle Biopsy. (November 2013) - Unal, Ozlem; Orhan, Diclehan; Ostergaard, Elsebet; Tokatli, Aysegul; Dursun, Ali; Ozturk-Hismi, Burcu; Coskun, Turgay; Wibrand, Flemming; Kalkanoglu-Sivri, H. Serap
Nemaline rods are the pathologic hallmark of nemaline myopathy, but they have also been described as a secondary phenomenon in a variety of other disorders. Nemaline rods have not been reported in pyruvate carboxylase deficiency before. Here we present a patient with pyruvate carboxylase deficiency and nemaline rods detected on muscle biopsy. The nemaline rods may be due to cellular energy shortage and altered energy metabolism in pyruvate carboxylase deficiency, similar to that in the previously reported patients. The mechanism of nemaline rod formation may be associated with the role of pyruvate carboxylase in cellular energy pathways.